A genetic screen for plant mutants with altered nodulation phenotypes in response to rhizobial glycan mutants. Issue 2 (30th June 2018) - Liu, Huijun; Sandal, Niels; Andersen, Kasper R.; James, Euan K.; Stougaard, Jens; Kelly, Simon; Kawaharada, Yasuyuki
Summary: Nodule primordia induced by rhizobial glycan mutants often remain uninfected. To identify processes involved in infection and organogenesis we used forward genetics to identify plant genes involved in perception and responses to bacterial glycans. To dissect the mechanisms underlying the negative plant responses to the Mesorhizobium loti R7AexoU and ML001cep mutants, a screen for genetic suppressors of the nodulation phenotypes was performed on a chemically mutagenized Lotus population. Two mutant lines formed infected nitrogen‐fixing pink nodules, while five mutant lines developed uninfected large white nodules, presumably altered in processes controlling organogenesis. Genetic mapping identified a mutation in the cytokinin receptor Lhk1 resulting in an alanine to valine substitution adjacent to a coiled‐coil motif in the juxta‐membrane region of LHK1. This results in a spontaneous nodulation phenotype and increased ethylene production. The allele was renamed snf5, and segregation studies of snf5 together with complementation studies suggest that snf5 is a gain‐of‐function allele. This forward genetic approach to investigate the role of glycans in the pathway synchronizing infection and organogenesis shows that a combination of plant and bacterial genetics opens new possibilities to study glycan responses in plants as well as identification of mutant alleles affecting nodule organogenesis.